2018
DOI: 10.5435/jaaos-d-16-00362
|View full text |Cite
|
Sign up to set email alerts
|

Management of Pediatric Femoral Neck Fracture

Abstract: In the pediatric population, femoral neck fracture is a relatively uncommon injury with a high complication rate, despite appropriate diagnosis and management. The anatomy and blood supply of the proximal femur in the skeletally immature patient differs from that in the adult patient. Generally, these fractures result from high-energy trauma and are categorized using the Delbet classification system. This system both guides management and aids the clinician in determining the risk of osteonecrosis after these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
73
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(100 citation statements)
references
References 38 publications
0
73
0
9
Order By: Relevance
“…The main criterion for choosing surgical access and implant was bone anatomy and the presence of active growth zones. [2,4,6]. It is known that at the age of about 4 to 6 years, ossification of the greater trochanter of the femur occurs, almost complete ossification of the femoral head (except its medial surface) and the ossification of the femoral neck ends.…”
Section: A T E R I a L S A N D M E T H O D Smentioning
confidence: 99%
See 1 more Smart Citation
“…The main criterion for choosing surgical access and implant was bone anatomy and the presence of active growth zones. [2,4,6]. It is known that at the age of about 4 to 6 years, ossification of the greater trochanter of the femur occurs, almost complete ossification of the femoral head (except its medial surface) and the ossification of the femoral neck ends.…”
Section: A T E R I a L S A N D M E T H O D Smentioning
confidence: 99%
“…If surgical treatment of such fractures is necessary, the question arises of choosing a method for fixation of fragments. [2,4,6].…”
Section: Introductionmentioning
confidence: 99%
“…Hip fractures represent less than 1% of pediatric fractures [1][2][3][4]. It is usually the result of high-energy injury.…”
Section: Introductionmentioning
confidence: 99%
“…It is usually the result of high-energy injury. Previous studies have reported a high risk of severe complications following a pediatric hip fracture [1][2][3][4][5][6][7][8]. As a result of anatomical differences, the complications observed in pediatric patients with hip fracture tend to different from those in adults, making this specific patient population and proper surgical management essential to characterize.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation